Hypophosphataemia, fibroblast growth factor 23 and third-generation intravenous iron compounds: a narrative review - Xenophon Kassianides; Sunil Bhandari (Drugs in Context, 2021)
Third-generation intravenous (i.v.) iron preparations are safe and efficacious and are increasingly used in the treatment of iron-deficiency anaemia. Hypophosphataemia is emerging as an established side-effect following the administration of certain compounds. Symptoms of hypophosphataemia can be masked by their similarity to those of iron-deficiency anaemia and both acute and chronic hypophosphataemia can be detrimental. Hypophosphataemia appears to be linked to imbalances in the metabolism of the phosphatonin fibroblast growth factor 23. In this narrative review, we discuss the possible pathophysiology behind this phenomenon, the studies comparing third-generation i.v. iron compounds, and the potential implications of the changes in fibroblast growth factor 23 and hypophosphataemia. We also present an algorithm of how to approach such patients requiring i.v. iron in anticipation of hypophosphataemia and how the impact related to it can be minimized.